2012
DOI: 10.1148/radiol.11110888
|View full text |Cite
|
Sign up to set email alerts
|

Bosniak Category IIF and III Cystic Renal Lesions: Outcomes and Associations

Abstract: Although the malignancy rate in surgically excised Bosniak IIF and Bosniak III cystic renal lesions was 25% and 54%, respectively, in our study, the malignancy rate was higher in patients with a history of primary renal malignancy or coexisting Bosniak IV lesion and/or solid renal neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 19 publications
4
72
1
8
Order By: Relevance
“…Bosniak classification can predict the risk of malignancy (LE 3) and provide guidance for management [25]. Bosniak 1, 2, 2F, 3, and 4 cysts are malignant in 0%, 0%, 25%, 54%, and 100% of cases, respectively [26].…”
Section: Imagingmentioning
confidence: 99%
“…Bosniak classification can predict the risk of malignancy (LE 3) and provide guidance for management [25]. Bosniak 1, 2, 2F, 3, and 4 cysts are malignant in 0%, 0%, 25%, 54%, and 100% of cases, respectively [26].…”
Section: Imagingmentioning
confidence: 99%
“…67 Given their relatively indolent nature, there is emerging evidence suggesting that these lesions (especially Bosniak classification III) can be safely managed by active surveillance. 6,12,13,29,31,32,35,38,41,48,59 Extrapolating from data on SRMs, Bhatt et al have suggested that Bosniak III and perhaps even Bosniak IV cysts with a solid component measuring less than 3 cm could be managed with initial surveillance. 67 Nevertheless, given the paucity of data, this management strategy should be reserved for well-informed patients and generally for patients at high surgical risk due to comorbidities or limited life expectancy.…”
Section: Bosniak Category IVmentioning
confidence: 99%
“…It is reported that Bosniak I, II, IIF, III, and IV cysts were malignant in 0, 0, 25, 54, and 100% of cases, respectively [26] . Due to the low probability of Bosniak I and II cysts being malignant, surgery is deemed unnecessary.…”
Section: Discussionmentioning
confidence: 98%